Individual Differences as Predictors of Social Networking. Issue 3 (1st April 2014) - Orchard, Lisa J.; Fullwood, Chris; Galbraith, Niall; Morris, Neil
Abstract: Research suggests that personality dictates specific Internet preferences. One area that remains relatively unexplored is the influence of personality on engagement with social networking sites (SNSs). The current study employs a 'Uses and Gratifications' framework to investigate whether personality, age, and sex predict motivations for using SNSs. The study explores both global and specific factors of personality using Eysenck's EPQ-R short form (extraversion, neuroticism and psychoticism) and Beck's SAS (sociotropy and autonomy). Principal component analysis identified ten distinct motivational components, which were then successfully predicted by individual differences through regression analyses. It is therefore suggested that individuals with different profiles vary in their motivations for using SNSs. Results support theoretical assumptions based on previous literature and personality dispositions.